2010
DOI: 10.1111/j.1365-4632.2010.04550.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐DR6 association confers increased resistance to T. rubrum onychomycosis in Mexican Mestizos

Abstract: These results suggest that HLA-DR6 confers protection against the development of onychomycosis in a Mexican Mestizo population. Having an affected first-degree relative significantly increases the risk of onychomycosis, suggesting genetic susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 30 publications
0
15
0
4
Order By: Relevance
“…Family history is also believed to be a risk factor (Ghannoum et al, 2013), and pedigree analysis has shown autosomal dominant inheritance of T. rubrum susceptibility (Zaias et al, 1996). Genetic association studies have shown that susceptibility to T. rubrum onychomycosis is reduced by the presence of HLA DR53 and DR6 alleles (Zaitz et al, 1996;Asz-Sigall et al, 2010) but increased by HLA-DR8 (García-Romero et al, 2012). In addition, a À 44C/G polymorphism in the defensin beta (DEFB) 1 gene is correlated with increased fungal carriage (Jurevic et al, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…Family history is also believed to be a risk factor (Ghannoum et al, 2013), and pedigree analysis has shown autosomal dominant inheritance of T. rubrum susceptibility (Zaias et al, 1996). Genetic association studies have shown that susceptibility to T. rubrum onychomycosis is reduced by the presence of HLA DR53 and DR6 alleles (Zaitz et al, 1996;Asz-Sigall et al, 2010) but increased by HLA-DR8 (García-Romero et al, 2012). In addition, a À 44C/G polymorphism in the defensin beta (DEFB) 1 gene is correlated with increased fungal carriage (Jurevic et al, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…HLA-DR6 fand sich bei 7 von 21 mexikanischen Mestizen mit Onychomykose (33 %), jedoch immerhin bei 45 % der Kontrollen [27]. Sechs Patienten (29 %) und 3 Kontrollen (7 %) hatten Kinder mit einer Nagelinfektion.…”
Section: Genetische Disposition Für Eine Onychomykoseunclassified
“…In einer prospektiven Fall-Kontroll-Studie wurde kürzlich dieser Zusammenhang zum HLA-DR4 bei mexikanischen Mestizen untersucht [2]. HLA-DR6 fand sich bei 7 von 21 Patienten mit OM (33%), jedoch immerhin bei 19 (45%) der 42 Kontrollen.…”
Section: Genetische Disposition Für Eine Onychomykoseunclassified